Metal nanopowders : production, characterization, and energetic applications - Gromov, Alexander; Teipel, Ulrich (Wiley-VCH Verlag, 2014)
Written with both postgraduate students and researchers in academia and industry in mind, this reference covers the chemistry behind metal nanopowders, including production, characterization, oxidation and combustion. The contributions from renowned international scientists working in the field detail applications in technologies, scale-up processes and safety aspects surrounding their handling and storage.